Effect of use of regional financial management information systems on individual performance in BPKAD Sikka Regency - Jaeng, Wihelmina Maryetha Yulia; Suardikha, I Made Sadha; Budiasih, I. G. A. N. (International research journal of management, IT and social sciences, 2019)
The Regional Financial Management Information System (SIPKD) is an integrated application that is used as a tool for the Regional Financial and Asset Management Agency of Sikka Regency in carrying out financial management activities so that it is able to produce financial reports of the local government. Testing the measurement of SIPKD success using the DeLone and McLean (2003) models. This study examines the effect of collaboration quality, information quality, system quality on the use of SIPKD and the effect of using SIPKD on individual quality. The sampling technique uses purposive sampling with criteria for all SIPKD users in BPKAD Sikka Regency, as many as 51 people. Data collection using a questionnaire distributed to BPKAD Sikka Regency. Data analysis using Partial Least Square 3.2.8. The results showed that the quality of collaboration, information quality, system quality has a positive effect on the use of SIPKD. The use of SIPKD has a positive effect on individual performance.